2022
DOI: 10.3389/fnut.2021.809328
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Harmonized Food Consumption Data Collection in the Balkan Region According to the EFSA EU Menu Methodology Standards

Abstract: Initiatives in the Capacity Development in Nutrition Research in the Balkan region in the last decade have been toward the creation of contemporary, harmonized Research Infrastructure (RI) compliant with European standards. This study describes the process of creation and implementation of the European Food Safety Authority (EFSA) EU Menu methodology in the Balkan region during the EFSA support projects for food consumption data collection in four countries (Serbia, Montenegro, Bosnia and Herzegovina, and Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The National Food Consumption Survey on toddlers and children, in compliance with the EFSA EU Menu methodology [33,34], was conducted between 2017 and 2021 and included a total of 576 participants, comprising 290 toddlers aged from 1 to 2.9 years old and 286 children aged from 3 to 9 years old. Data collected included: general questionnaire, body weight and height measurements, age-appropriate Food Propensity Questionnaire (FPQ), and twice repeated 24 h food record.…”
Section: National Food Consumption Survey On Toddlers and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Food Consumption Survey on toddlers and children, in compliance with the EFSA EU Menu methodology [33,34], was conducted between 2017 and 2021 and included a total of 576 participants, comprising 290 toddlers aged from 1 to 2.9 years old and 286 children aged from 3 to 9 years old. Data collected included: general questionnaire, body weight and height measurements, age-appropriate Food Propensity Questionnaire (FPQ), and twice repeated 24 h food record.…”
Section: National Food Consumption Survey On Toddlers and Childrenmentioning
confidence: 99%
“…Additionally, the study sample was stratified to proportionally cover weekdays and weekend days, capturing variability of dietary patterns. According to EFSA EU Menu methodology, food consumption data collection studies are performed using twice repeated 24 h records [33]. Total exposure from nitrites and phosphate-total EDI-could not be extracted in this study, as only consumption of processed meat products was observed.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Data on the frequency of consumption of certain food groups and dietary supplements over the past year and level of physical activity over the past week were collected by a trained medical doctor using a food propensity questionnaire (FPQ) in accordance with the European Food Safety Authority (EFSA) EU Menu methodology ( 49 , 50 ) and the International Physical Activity Questionnaire – Short Form (IPAQ-SF) ( 51 ). Data on the frequency of consumption of certain food groups and dietary supplements over the past year were categorised into seven categories: 1) never; 2) less than once a month; 3) one to three times a month; 4) once a week; 5) two to three times a week; 6) four to five times a week; and 7) six to seven times a week.…”
Section: Methodsmentioning
confidence: 99%
“…The Serbian Food Consumption Survey methodology details have been previously published [ 11 ]. In brief, the study was conceptualized and conducted in compliance with principles, established protocols, and guidelines of the EU Menu project between 2017 and 2021 [ 12 , 13 ]. The nationally representative sample comprised children residing in private households in the territory of the Republic of Serbia and was classified into two subgroups: (1) one- to three-year-old toddlers, and (2) three to nine year-old-children.…”
Section: Methodsmentioning
confidence: 99%